Antimicrobial Efficacy of CdFe2O4/Fe2O3 Nanocomposite Against Extensively Drug-Resistant Pseudomonas aeruginosa: Influence of Calcination Temperature and Crystalline Phases - Smail, Abdalla Mohammed; Babakr, Karukh Ali; Qurbani, Karzan; Pekdemir, Sibel Selcuk; Qader, Ibrahim Nazem; Hamid, Dlshad Aziz; Kok, Mediha (Springer, 2025)
CdFe(2)O(4)NPs show promise in addressing antimicrobial development and microbial resistance, highlighting the need for further research to fully harness their biological potential. This study aims to investigate the effects of calcination temperature and the incorporation of dopant elements (Cu and Sr) into CdFe2O4 nanoparticles (NPs) on their antimicrobial activity against extensively drug-resistant (XDR) bacteria and biofilms. The biological performance of the nanoparticles is analyzed by correlating their physical and chemical properties with antimicrobial efficacy. X-ray diffraction (XRD) analysis revealed that the NPs' formation and crystal structure strongly depends on the calcination temperatures. Thermogravimetric analysis (TG) indicated that higher calcination temperatures reduced mass loss, suggesting stronger chemical bonding and a decrease in the surface-to-volume ratio, enhancing nanoparticle stability. Antimicrobial testing against Pseudomonas aeruginosa XDR strains showed that calcination temperature significantly influenced antibacterial activity. Samples calcined at 500 degrees C and 700 degrees C exhibited inhibition zones, with 90% inhibition (MIC90) at 100 mu g/mL for the 700 degrees C-calcined samples. The minimum bactericidal concentration (MBC) for all active samples was 200 mu g/mL. Regarding antibiofilm activity, all samples reduced biofilm formation by over 50%, with the undopped sample calcined at 700 degrees C showing the highest efficacy, achieving 100% biofilm reduction at 60 mu g/mL. In conclusion, the NPs calcined at 700 degrees C exhibit enhanced antibacterial and antibiofilm properties, likely due to their optimized surface characteristics and crystalline structure, making them promising candidates for combating XDR bacterial infections. Their improved physicochemical properties, including crystallinity and surface characteristics, contribute to their effectiveness in disrupting bacterial biofilms and inhibiting bacterial growth.
Keywords: Hematite; Cadmium ferrite; Nanoparticles; Antibiotic